International Conference on Space Optics — ICSO 2018 2019
DOI: 10.1117/12.2536068
|View full text |Cite
|
Sign up to set email alerts
|

Advances in IBS Coatings for space applications on the topics of curved surfaces and laser damage

Abstract: IBS Coatings are a good candidate for high performance applications. They are hard, dense, exhibit a small thermal shift, and have the best scattering and surface roughness performance of the various coating technologies. In addition, they feature a highly stable refractive index for the coated materials allowing the production of complex coatings. Because of their high density and resistance towards high energy radiation IBS coatings are also well suited for space applications. For high power laser applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Ion beam sputtering (IBS) [13] is a deposition method of interference coating with a high LIDT value and dense films with a high-refractive index, which are also characterized by high LIDT values [14][15][16][17]. The IBS method mainly sputters a pure metal target (Ta, Nb, Al, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Ion beam sputtering (IBS) [13] is a deposition method of interference coating with a high LIDT value and dense films with a high-refractive index, which are also characterized by high LIDT values [14][15][16][17]. The IBS method mainly sputters a pure metal target (Ta, Nb, Al, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Optical films of the highest quality are often produced by energetic processes like ion‐beam sputtering (IBS) or magnetron sputtering, and the as‐grown films are generally submitted to postdeposition annealing to further improve their optical and mechanical performance. [ 1–5 ] It has been observed that postdeposition annealing of amorphous oxide thin films often reduces the optical absorption at sub‐bandgap energies until the onset of crystallization. Similarly, postdeposition annealing changes the mechanical loss (also known as internal friction) of thin films in a way that depends on the structure of the material.…”
Section: Introductionmentioning
confidence: 99%